Phytochemical Investigation and B Ioactivity Screening of Vitex (Verbenaceae) and Ficus (Moraceae) Species - Dafalla, Hassan Abdalla Almahy (2002)
The study on Vitex longisepala involves extraction, various chromatographic methods and structural determination by spectroscopic techniques such as IR, compounds were also elucidated by comparison with the previous works. works on leaves and bark of the plant yielded cholesterol (51),para-hydroxybenzoic acid (52), terpene. Crude extracts and isolated compounds from two parts of this plant were screened for antimicrobial activity using disc diffusion method and cytotoxic activity by using microtitration method. compouds exhibited antimicrobial activity against Gram-possitive and Gram-negative bacteria Cholesterol exhibited significant cytotoxic activity against T-lymphoblastic leukemic cell line with IC₅₀ 10 µg/ml. not show any antimicrobial activity against fungi. The methanol crude extract of the bark failed to show any significant antimicrobial activity, while the petroleum ether and the chloroform crude extracts of the bark exhibited weak antimicrobial activity against Bacillus cereus. The study on Vitex quinata involved the same procedure adopted above. Isolation works on the leaves and bark of the plant yielded cholesterol (51), 13- sitosterol (57), para-hydroxybenzoic acid (52), fructose (53), glucose (58), catechin (55), quercetin (59) and quercitrin (60). However, the bark of the plant yielded a mixture of long-chain compound, fatty acid and unidentified terpene. The crude extracts and isolated compounds of this plant were tested for antimicrobial and cytotoxic activity using disc diffusion and microtitration methods respectively. The crude extracts and pure isolated compounds exhibited positive antimicrobial results against two bacteria organisms and negative results against four fungi. Cholesterol and β-sitosterol gave cytotoxic activity against T -lymphoblastic leukemic cell line with IC₅₀ 10 and 25 µg/ml respectively. Detail investigation on the leaves, bark and fruits of Ficus benjamina has resulted in the isolation of seven compounds. The structure of these compounds were elucidated by means of spectroscopic methods including by the extensive use of various NMR techniques and also comparison with previous studies. The use of High Field NMR is essential in structural determination of these complex molecules. With the aids of various NMR experimental techniques and oth er spectroscopic methods such as IR, UV and MS, the correct structures of the pure isolated compounds were established. (63), The presence of bioactive compounds in th is plant was detected by the use of antimicrobial organism. crude plant extracts or pure isolated compounds could be determined. of chloroform and methanol extracts of the leaves of Ficus benjamina gave no significant activity while caffeic acid gave IC₅₀ value of 25 µg/ml. Phytochemical studies on leaves and bark of Ficus elastica have resulted in the isolation of emodin (66), (70) together with long-chain fatty acids. were established based on spectral studies using different spectroscopic methods and on comparison with published data.